Pemberdayaan Siswa dan Siswi SMAN 1 Labuapi Melalui Pembuatan Apotik Hidup: - - Nina Ara Febriani; Diyah Nurmayanti; Heru Setiawan; Raden Roro Theresia Nirbita Cahya Widya Puspita Amarillis; elya suci nabila (Universitas Mataram, 2026)
Indonesia possesses a rich diversity of medicinal plants with strong potential to be utilized as learning resources and as support for health through the concept of a living pharmacy. However, the use of school land as an environment- and character-based learning medium has not yet been optimized. This activity aimed to optimize the utilization of vacant land at SMAN 1 Labuapi through the establishment and use of a living pharmacy as a contextual learning medium and as a means of strengthening students’ sense of responsibility. The method employed was empowerment, involving active student participation at all stages of the activity, including site observation, land preparation, planting, installation of plant name boards, and maintenance of medicinal plants. The results showed that the living pharmacy was successfully developed and received positive responses from the school community. Students’ direct involvement in the activity enhanced their environmental awareness, knowledge of medicinal plants, and the development of responsible character. In addition to providing health and environmental benefits, the living pharmacy also functions as an educational and sustainable learning medium. Therefore, the utilization of a living pharmacy in the school environment has the potential to serve as an alternative form of environment-based learning that supports character strengthening and health literacy among students.